경기 일부지역 대학생의 섬유소 섭취 행동단계에 따른 영양소 섭취상태 비교 - 정은정(Eun Jung Chung) (Korean journal of community nutrition, 2005)
This study was conducted to compare nutrient intakes regarding stages of change in dietary fiber increasing behavior. Subjects were consisted of healthy 383 college students (2S0 females and 133 males) in Kyunggi-Do. Stages of change classified by an algorithm based on 6 items were designed each subjects into one of the 5 stages: precontemplation (PC), contemplation (CO), preparation (PR), action (AC), maintenance (MA). Nutrient intakes were assessed by 24-hr recall method. Regarding the S stages of changes, PR stage comprised the largest group $(39.4%)$, followed by AC $(33.7%)$, MA$(14.6%)$, PC$(7.6%)$, CO$(34.7%)$. Female were more belong to either AC or MA. The higher stage of change in dietary fiber increasing behavior, the higher self-efficacy. In all male and female, there were no differences in energy, protein, monounsaturated fatty acids, polyunsaturated fatty acids and cholesterol intakes across the 5 stages. But, fiber, postassuim (K), vitamin A and vitamin C intakes of AC or MA were higer than those of PC, CO and PR $Energy%$ from fat of $PR(25.4\~26.5%)$ was higher than $20%$, and those of AC and MA was lower than the other groups. Dietary P/S and ${ε}6/ε$ 3 ratios of AC and MA were similar to the recommended ratio. Female of PR had the most total saturated fat and palmitic acid and those of MA had the least. Male of PR had the least $α-LNA\;({ε}3)$ and total ${ε}3$ fatty acids and those of MA had the most. In male and female in AC or MA, fiber and K intakes from breakfast, dinner and snack and vitamin C intakes from all meals were higher than those of the other stages. These results of our study confirm differences in stages of change in fiber intake in terms of nutritional status. To have lower $energy%$ from fat, higher intakes of K, fiber and vitamins, desirable ratio of dietary fatty acids, it needs consistent nutritional education leading to the AC or MA of fiber increasing behavior.